Navigating Wound Closure Strategies: Primary Closure vs. Delayed Primary Closure in Digestive Surgery—A Systematic Review and Meta-Analysis on Surgical Site Infections - Sihardo, Lam; Lalisang, Arnetta NL; Putra, Afid B; Suryawiditya, Bagus A (The New Ropanasuri Journal of Surgery, 2024)
Introduction. Surgical site infection (SSI) is a significant concern following digestive surgery, with varying incidence rates based on wound contamination levels. The choice between Primary Closure (PC) and Delayed Primary Closure (DPC) impacts SSI occurrence, making it essential to evaluate their comparative effectiveness. DPC is hypothesized superior to PC to prevent SSI or wound infection after a contaminated abdominal surgery. Methods. This systematic review study was carried out through PubMed, Scopus, and Cochrane (CENTRAL). Quality was assessed using Risk of Bias (ROB-2) tool. All results were summarized, and quantitative analysis was performed using a random-effect model. This study is reported following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Eligibility criteria included adult patients undergoing abdominal gastrointestinal surgery, evaluating SSI and hospital stay, directly comparing PC and DPC, and randomized controlled trials (RCT) study. Results. Of 447 published studies, there were 10 eligible RCTs, consist of 672 subjects who received DPC and 668 subjects who received PC. We found no significant difference in SSI occurrence between PC and DPC (RR=0.62, 95%CI: 0.38–1.02; p=0.06) with high heterogeneity (I2=74%, p Conclusion. DPC tend to decrease SSI risk. Our findings revealed that PC is not inferior than DPC to prevent SSI and improve hospital stay in abdominal surgery. The choice between techniques should be individualized, considering patient characteristics and surgical context. Standardized criteria and further research are crucial for refining closure method selection, ultimately enhancing patient outcomes and reducing the burden of SSI.